Respuesta :

Answer:

y = 9.75

Step-by-step explanation:

(4y - 3)2 = 72

Opening the brackets;

8y - 6 = 72

8y = 72 + 6 = 78

y = 78 ÷ 8 = 9.75

Answer:

[tex]y = \frac{3+6\sqrt{2}}{4}\text{ and } y = \frac{3-6\sqrt{2}}{4}[/tex]

Step-by-step explanation:

Given quadratic equation,

[tex](4y-3)^2=72[/tex]

[tex]\implies 4y - 3 = \pm \sqrt{72}[/tex]   ( Taking root on both sides )

[tex]4y=3 \pm 6\sqrt{2}[/tex]     ( Additive property of equality ),

[tex]y = \frac{3 \pm 6\sqrt{2}}{4}[/tex]   ( Division property of equality )

[tex]\implies y = \frac{3+6\sqrt{2}}{4}\text{ or }y =\frac{3-6\sqrt{2}}{4}[/tex]

Hence, the solution of the given equation is,

[tex]\implies y = \frac{3+6\sqrt{2}}{4}\text{ and }y =\frac{3-6\sqrt{2}}{4}[/tex]